SISTEM PENDUKUNG KEPUTUSAN PROGRES MAHASISWA MAGANG DENGAN METODE SAW - Salsabil, Aditya Brian; Muhtarom, Moh; Nurohman, Nurohman (TEKNOKOM, 2024)
This research is a form of a decision support system that raises from a case study at the company PT Semesta Ruang Inovasi which is engaged in the world of technology, with a problem in determining the best candidate candidates from internship students the previous year or month who have standard assessment criteria determined by a weight value. the final results of the SAW method process still enter the initial design material before developing an application such as a website or mobile. The decision support system in this study certainly requires a Simple Additive Weighting (SAW) method as a calculation technique. the results of this study are intended as initial design material before developing an application such as a website or mobile. the final result of the SAW method process still enters the classification value based on company standards set with several types of categories. it is hoped that this research can be further developed according to similar case studies.